2016
DOI: 10.1016/j.celrep.2016.09.076
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Activates Proinflammatory Signaling via TLR5 Leading to Allodynia

Abstract: SUMMARY Infectious and sterile inflammatory diseases are correlated with increased levels of high mobility group box-1 (HMGB1) in tissues and serum. Extracellular HMGB1 is known to activate toll-like receptors (TLRs) 2, 4 and RAGE (receptor for advanced glycation endproducts) in inflammatory conditions. Here we find that TLR5 is also an HMGB1 receptor that was previously overlooked due to lack of functional expression in the cell lines usually used for studying TLR signaling. HMGB1 binding to TLR5 initiates NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 59 publications
3
86
0
Order By: Relevance
“…An in vitro study demonstrated that pharmacological inhibition of TLR-4 or MyD88 also inhibited HMGB1-induced proinflammatory cytokine production [39]. Furthermore, it has been demonstrated that HMGB1 induces proinflammatory cytokine production in vivo via the TLR-4-MyD88-NF-κB pathway [40] (Fig. 2).…”
Section: Hmgb1 Signaling For the Initiation Of Different Diseasesmentioning
confidence: 92%
“…An in vitro study demonstrated that pharmacological inhibition of TLR-4 or MyD88 also inhibited HMGB1-induced proinflammatory cytokine production [39]. Furthermore, it has been demonstrated that HMGB1 induces proinflammatory cytokine production in vivo via the TLR-4-MyD88-NF-κB pathway [40] (Fig. 2).…”
Section: Hmgb1 Signaling For the Initiation Of Different Diseasesmentioning
confidence: 92%
“…An in vitro study demonstrated that blocking TLR4 or MyD88 inhibited HMGB-1-induced proinflammatory cytokine production in mouse tracheal epithelial cells [58]. Furthermore, Das et al found that the interaction of HMGB-1 and TLR5 initiated NF-κB activation via MyD88, resulting in proinflammatory cytokine production in vivo [59]. These findings indicated that HMGB-1 exhibited its proinflammatory effect via the MyD88-dependent pathway by binding to its receptors.…”
Section: Figmentioning
confidence: 99%
“…TLR5 is reported to express in a large range of cell types, and an agonist of TLR5 has various immunomodulatory influence on innate and adaptive immunity . High mobility group box‐1 protein (HMGB 1) can activate proinflammatory signaling through TLR5 and result in allodynia . It has been reported that TLR5 can open the door to the treatment of neuropathic pain .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 High mobility group box-1 protein (HMGB 1) can activate proinflammatory signaling through TLR5 and result in allodynia. 24 It has been reported that TLR5 can open the door to the treatment of neuropathic pain. 25 Mechanical allodynia is inhibited in neuropathic pain by inhibiting TLR5mediated A-fiber.…”
mentioning
confidence: 99%